UPAYA PENINGKATAN MOTIVASI DAN HASIL BELAJAR MELALUI PENDEKATAN KOOPERATIF MODEL COURSE REVIEW HORAY SISWA KELAS XII.2 PADA MATA PELAJARAN ANALISIS INSTRUMEN - Netri Elisma (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
UV Vis Spectrophotometry is one of the learning materials that are difficult for students to understand because of the abstract concept. This difficulty in understanding can affect the further development of student knowledge. This research describes the learning process through a cooperative approach to the Course Review Horay model. The method used is a class action research method on one of the research subjects 17 students of class XII.2 SMK SMTI Padang. The research objectives were achieved with instruments in the form of learning descriptions, class observations, interviews, diagnostic tests and final tests. The results showed that the learning process at each stage went well. The understanding of students in the concept understanding category has increased classical completeness from 68.75% to 93.25%. Student responses to the application of a cooperative approach to the course review horay model are very positive. Suggestions put forward that this method can be used to visualize abstract photometric or spectrophotometric concepts and can minimize misconceptions. Giving examples in everyday life can improve students' understanding, and motivate students to follow the learning process.